2016
DOI: 10.4103/2277-9175.190935
|View full text |Cite
|
Sign up to set email alerts
|

Life stressors, coping strategies, and social supports in patients with irritable bowel syndrome

Abstract: Background:The frequency and the perceived intensity of life stressors, coping strategies, and social supports are very important in everybody's well-being. This study intended to estimate the relation of irritable bowel syndrome (IBS) and these factors.Materials and Methods:This was a cross-sectional study carried out in Isfahan on 2013. Data were extracted from the framework of the study on the epidemiology of psychological, alimentary health, and nutrition. Symptoms of IBS were evaluated by Talley bowel dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…We observed that the frequency of anxiety had a similar trend to that of IBS with respect to the level of education. Therefore, we concluded that highly educated participants in our study had more anxiety, which is an established risk factor for IBS [ 17 , 29 ]. Accordingly, an important step for alleviating the educational inequality in IBS would seem to be to pay special attention to the identification and elimination of the sources of stress in people with a high level of education.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We observed that the frequency of anxiety had a similar trend to that of IBS with respect to the level of education. Therefore, we concluded that highly educated participants in our study had more anxiety, which is an established risk factor for IBS [ 17 , 29 ]. Accordingly, an important step for alleviating the educational inequality in IBS would seem to be to pay special attention to the identification and elimination of the sources of stress in people with a high level of education.…”
Section: Discussionmentioning
confidence: 94%
“…Costanian et al [ 28 ] observed this finding as well. According to Roohafza et al [ 29 ], educational concerns are an important group of life stressors, which along with job-related stressors could significantly predict IBS occurrence. There do not seem to be a sufficient number of suitable occupations for highly educated people in places like Kish Island.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies showed that IBS patients used more problemfocused coping (PFC) strategies than HC [15,23]. Patients with IBS have less social support, less-adapted coping strategies, and perceived life stressors as more intense and frequent [19]. A study performed by van der Veek et al [31] analyzed the relation between visceral hypersensitivity and psychological factors in IBS.…”
Section: Ibs Patients Versus Healthy Controlsmentioning
confidence: 99%
“…Emotion-focused coping strategies such as distraction and suppression behaviors were significantly associated with somatic symptoms, and depressed affect [12,19,20,22,30,31]. This type of coping behaviors was associated with increased self-blame and poor psychological outcome.…”
Section: Ibs Patients Versus Healthy Controlsmentioning
confidence: 99%
“…32,33 Patients with IBS reported having less social support than those with no symptoms. 34,35 In the current study, those with stable and improved IBS symptoms showed a trend towards better social well-being. Interestingly, Zhang and Ma 36 found that during COVID-19, participants reported increased social support from family and friends.…”
Section: Discussionmentioning
confidence: 46%